2010
DOI: 10.4103/0976-237x.72775
|View full text |Cite
|
Sign up to set email alerts
|

Hypohyperdontia: Agenesis of three third molars and mandibular centrals associated with midline supernumerary tooth in mandible

Abstract: Agenesis of teeth in a patient who also presents with a supernumerary tooth is one of the rare numerical anomalies in human dentition. Agenesis of third molars was shown to be associated with other missing permanent teeth. A review of literature on hypodontia including third molar agenesis, hyperdontia and a concomitant presence of these two conditions which is termed as hypohyperdontia is presented along with a case showing agenesis of three third molars, both mandibular central incisors and a midline supernu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 27 publications
(37 reference statements)
2
28
0
Order By: Relevance
“…The average age of the reported patients was 11.29 years. Based on occurrence, the bimaxillary type (65%) was the most commonly reported (2)(3)(4)(5)(6)13,16,17, followed by the maxillary (21%) type (1,3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and mandibular (14%) type (3,16,(19)(20)(21)(22)(23)(24)(25)(26)(27), the results being statistically significant (P < 0.001) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average age of the reported patients was 11.29 years. Based on occurrence, the bimaxillary type (65%) was the most commonly reported (2)(3)(4)(5)(6)13,16,17, followed by the maxillary (21%) type (1,3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and mandibular (14%) type (3,16,(19)(20)(21)(22)(23)(24)(25)(26)(27), the results being statistically significant (P < 0.001) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although ample literature has exclusively described hypodontia or hyperdontia, only a few surveys have reported the occurrence of hypo-hyperdontia (5,6,23,49). It has been suggested that hypodontia and hyperdontia represent opposite ends of the developmental scale for dentition (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this condition in the same area of mandibular anterior region is reported very rarely. As discussed by Nuvvula et al, [3] and Marya et al, [4], in our case report also the possibility of a microdont central incisor with the congenitally missing contra lateral mandibular central incisor cannot be eliminated. However, this tooth can not be considered as central incisor as the shape of the crown of this midline tooth is distinctively conical that does not resemble to normal central incisor and also in comparison to mandibular lateral incisors its root formation is reduced.…”
mentioning
confidence: 49%
“…4 It has also been reported that the unilateral form of dental agenesis was more common than the bilateral version. 4,14,15 Single mandibular central incisor in mandible in has been reported and authors stated found the association with chromosome 18p. 16 Similarly, in the present case unilateral absence of central incisor was evident in both primary and permanent dentition.…”
Section: Discussionmentioning
confidence: 98%